2012
DOI: 10.1016/j.resp.2012.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of bone marrow mononuclear cell therapy on lung and heart in an elastase-induced emphysema model

Abstract: We hypothesized that bone marrow-derived mononuclear cell (BMDMC) therapy protects the lung and consequently the heart in experimental elastase-induced emphysema. Twenty-four female C57BL/6 mice were intratracheally instilled with saline (C group) or porcine pancreatic elastase (E group) once a week during 4 weeks. C and E groups were randomized into subgroups receiving saline (SAL) or male BMDMCs (2 × 10(6), CELL) intravenously 3h after the first saline or elastase instillation. Compared to E-SAL group, E-CEL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 51 publications
5
51
0
Order By: Relevance
“…Furthermore, IL-1β has been implicated in fibroblast activation and collagen deposition [33]. As already demonstrated in other models of lung inflammation and fibrosis [10], BMDCs were able to prevent an increase in the amount of TGF-β in lung tissue as well as TGF-β mRNA after instillation of silica [3]. TGF-β regulates a wide variety of cellular processes including cell growth, apoptosis, differentiation, migration, and extracellular matrix production [34].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, IL-1β has been implicated in fibroblast activation and collagen deposition [33]. As already demonstrated in other models of lung inflammation and fibrosis [10], BMDCs were able to prevent an increase in the amount of TGF-β in lung tissue as well as TGF-β mRNA after instillation of silica [3]. TGF-β regulates a wide variety of cellular processes including cell growth, apoptosis, differentiation, migration, and extracellular matrix production [34].…”
Section: Discussionmentioning
confidence: 94%
“…Several studies have reported on the beneficial effects of bone marrow cell therapy in different models of lung injury [5,6,7,8,9,10]. In experimental models of lung fibrosis, bone marrow-derived cells (BMDCs) were able to repair damaged tissue by modulating the inflammatory process and replacing damaged cells [3,5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is imperative to understand which cell populations in the BMDMCs might convey beneficial effects for use in any given disease. In preclinical models of lung diseases, BMDMCs have been shown to abrogate airway inflammation and remodeling and to promote lung repair in mouse models of acute lung injury, chronic obstructive pulmonary disorder, silicosis and asthma [2426, 32, 36, 58]. With respect to asthma, we have previously compared BMDMCs with MSCs in a mild Th2-mediated eosinophilic allergic airway disease induced by ovalbumin sensitization and challenge [12].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, either a small number of MSCs (i.e., the approximately 5 × 10 4 MSCs contained in the BMDMCs) was sufficient to mitigate the effect or another cell type in the BMDMC also played a role. Previous studies in other disease models have suggested that the functional effects of the BMDMCs result from a balance between different cell types, with potential beneficial involvement of all component cells [2426, 32, 36, 52, 53, 57, 58]. BMDMCs include a variety of cells: progenitor cells (hematopoietic progenitor cells and mesenchymal stromal cells), leukocytes (B and T lymphocytes, and monocytes/macrophages), and endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation